SAT0509 Clinical and Serological Profile of Children with Positive SSA-Ro/SSB-La Antibodies. (9th June 2015) - Ovalles-Bonilla, J.G.; Nieto, J.C.; Martinez-Barrio, J.; Lopez-Longo, F.J.; Janta, I.; Naredo, E.; Gonzalez, C.M.; Hinojosa, M.C.; Bello, N.; Serrano, B.; Mata-Martinez, C.; Gonzalez, R.; et al.
Abstract : Background: Several studies have shown the relationship between anti-SSA-Ro/SSB-La antibodies and Systemic Lupus Erythematosus (SLE), Sjögren Syndrome (SS) and other autoimmune diseases in adult population. However, the expression of these autoantibodies and clinical correlation in juvenile patients is poorly described. Objectives: To characterize the clinical and serological profile and primary rheumatic diseases in pediatric patients with positive anti-SSA-Ro and/or anti-SSB-La antibodies. Methods: The data was obtained from a long term prospective cohort of patients under age 18 diagnosed with rheumatic diseases in a tertiary hospital in Spain. Demographic, clinical, and laboratory data were collected from 1986 to 2010. Patients were divided into 2 groups: anti-SSA-Ro/SSB-La positive and anti-SSA-Ro/SSB-La negative. Results: A total of 187 patients were tested for anti Extractable Nuclear Antigens (ENA), with a following mean time of 11 years. Mean age at disease onset was 12.6 years and 77% were female. Fifty-four (28.9%) anti-SSA-Ro/SSB-La positive subjects were compared against 133 (71.1%) anti-SSA-Ro/SSB-La negative subjects. Among positive cases, 13 (24.1%) patients were double-positive for anti-SSA-Ro and anti-SSB-La, 51 (94.4%) were positive for anti-SSA-Ro and 3 (5.5%) were single-positive for anti-SSB-La. The anti-SSA-Ro/SSB-La antibodies were found less frequently (p=0.003) in the overlapping syndromes, and more frequently in SLE (p=0.007). In addition rheumatoid factor (p<0.001), anti-Sm (p<0.001) and anti-RNP (p<0.001) were frequently co-expressed with anti-SSA-Ro/SSB-La antibodies. Finally the anti-SSA-Ro/SSB-La positive group presented more hematological and skin manifestations than the negative group (p<0.05). Conclusions: Similarly to adults, we observed a relationship between anti-SSA-Ro/SSB-La antibodies and SLE in pediatric patients. However a low proportion of childhood primary SS exists in our anti-SSA-Ro/SSB-La positive cases. This could be explained by underdiagnoses related to the atypical clinical presentation of SS in pediatric population. Single-positive anti-SSB-La patients are uncommon, the clinical significance of this serological result remains uncertain in children. References: Rheumatol Int (2014) 34:1123–1127. Disclosure of Interest: None declared